0
$\begingroup$

I came across the following equation for differential change in enthalpy:

$$ dh = c_p dT + \frac{1-\beta T}{\rho}dP$$

where $\beta = -\frac{1}{\rho}(\partial \rho / \partial T)_P$ is the thermal expansion coefficient.

I would like to prove this equation for myself, but I'm stuck.

I start from

$$ dh = Tds + vdP$$

and use $c_p = T\frac{dS}{dT}$ which gives

$$ dh = c_pdT + vdP$$

but this implies that

$$ v = \frac{1-\beta T}{\rho}$$

if I want to approach the first equation. I don't see why this is true, if it's even true at all. How can I arrive at the first equation?

EDIT:

I'm gonna start with

$$ dh = Tds + vdP$$

and use a total differential for $ds$:

$$ds=C_P\frac{dT}{T}+\left(\frac{\partial s}{\partial P}\right)_TdP$$

Then use a Maxwell relation $\left(\frac{\partial s}{\partial P}\right)_T=-\left(\frac{\partial v}{\partial T}\right)_P$:

$$ds=C_P\frac{dT}{T}-\left(\frac{\partial v}{\partial T}\right)_PdP$$

where $\left(\frac{\partial v}{\partial T}\right)_P = \beta/\rho$. Now substitute this $ds$ into $dh$:

$$ dh = c_pdT + \frac{1-\beta T}{\rho} dP$$

$\endgroup$
2
$\begingroup$

Start with $$ds=\left(\frac{\partial s}{\partial T}\right)_PdT+\left(\frac{\partial s}{\partial P}\right)_TdP=C_P\frac{dT}{T}+\left(\frac{\partial s}{\partial P}\right)_TdP$$ Then, using the equation $$dG=-sdT+vdP$$show that $$\left(\frac{\partial s}{\partial P}\right)_T=-\left(\frac{\partial v}{\partial T}\right)_P$$ Finally, make use of the equation $$v=1/\rho$$

$\endgroup$
  • $\begingroup$ Ah I forgot about the Maxwell relation. That did it. $\endgroup$ – Drew Jan 24 at 3:18

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.